Dr. Dolittle - Thomas, Betty, 1949-; Murphy, Eddie, 1961-; Davis, Ossie; Platt, Oliver; Rock, Chris; Leguizamo, John.; MacDonald, Norm, 1963-; Brooks, Albert, 1947-; Shandling, Garry; DeGeneres, Ellen; Mauldin, Nat.; Levin, Larry; et al. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 1999)
A doctor finds out he can understand what animals are saying. When the animals find out, his world is turned upside down.
Based upon the Dr. Dolittle stories by Hugh Lofting.
Originally released as a motion picture.
Bonus feautres: interactive menus; scene selection and original theatrical trailer.
Director of photography, Russell Boyd; editor, Peter Teschner; music, Richard Gibbs.
Eddie Murphy, Ossie Davis, Oliver Platt ; voices of Chris Rock, John Legiuzamo, Norm MacDonald, Albert Brooks, Garry Shandling, Ellen DeGeneres.
Rated PG-13.
Keywords: Comedy films; Films for the hearing impaired; Feature films